Growth, mobility and social welfare - Dirk Van de Gaer; Flaviana Palmisano (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
We propose a social welfare function to evaluate a profile of income streams and compare the welfare gain of the actual profile relative to the income profile where the individual receives his first period income in each period. We derive necessary and sufficient conditions for the welfare gain to be positive, and show how this welfare gain can be decomposed in a pure effect of economic growth, a mobility effect and a cost due to aversion to time fluctuations given individuals' ranks in the income distribution. The mobility effect, generated by reranking in the income distribution has two components: a cost due to the time fluctuations in incomes and a benefit, due to the equalization in time averaged incomes. We illustrate the analysis using CNEF data for Australia, Korea, Germany and Switzerland. Our results indicate that the largest component of the welfare gain is the equalization of time averaged income, induced by reranking. After subtracting the cost of mobility due to the increase in time fluctuations of individual income streams, the net effect of mobility remains positive. In countries with high growth (Australia and Korea), the growth effect is larger than the mobility effect, but in countries with low growth (Germany and Switzerland), the opposite holds true.
Keywords: D31; D63; I32; 330; intertemporal growth; mobility; income streams; time horizon